Parameter Identification of Nonlinear System on Combustion Engine Based MVEM using PEM - Trigas Badmianto; Eka Firmansyah; Adha Imam Cahyadi (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2018)
In four-stroke engine injection system, often called spark ignition (SI) engine, the air-fuel ratio (AFR) is taken from the measurement of lambda sensor in the exhaust. This sensor does not directly describe how much AFR in the combustion chamber due to the large transport delay. Therefore, the lambda sensor is used only as a feedback in AFR control